Five new species of the genus Philydrodes Bernhauer, 1929 from China (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) - Shavrin, Alexey V. (Zootaxa, 2017)
Five new species of the subgenus Minyphilydrodes of the genus Philydrodes Bernhauer, 1929 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) from China are described and illustrated: Ph. tridentatus sp.n. (Hubei, Gansu, Shaanxi and Sichuan), Ph. tibetanus sp.n. (Yunnan), Ph. reticulatus sp.n. (Shaanxi), Ph. wrasei sp.n. (Sichuan) and Ph. michaeli sp.n. (Sichuan). The morphological features of Philydrodes, differences between Japanese and Chinese species, the relations of the genus with other taxa of the tribe Anthophagini Thomson, 1859 are briefly discussed. A key to the species of the genus from China and a distribution map are provided. The genus Philydrodes is recorded from continental Asia and China for the first time.